Personal Social Network as a Facilitating Tool for Collaborative Knowledge Construction - Cabezas, M. (2016)
This study addresses the way in which personal social networks could facilitate the collaborative construction of knowledge considering the potential o Collaborative Computer Assisted Learning (CSCL) as a resource. The state of the art of social networks in educational contexts is shown and methodological proposals to analyze interactions highlighting models used to identify both the way that knowledge is socially constructed as observable behavioral profile interactions, are mentioned. Objectives and the proposed research methodology are detailed. Likewise, the expected results and the possible contribution to the scientific world are stated. © 2016 ACM.